DESIGNING A BUSINESS INTELLIGENCE DASHBOARD FOR DEMAND-DRIVEN INVENTORY MANAGEMENT: A CASE STUDY OF MEDIKLUG PHARMACEUTICAL DISTRIBUTION COMPANY - Nicolaus Ernest Mamonto; Leo Aldianto (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
In pharmaceutical distribution, balancing high product variety with fluctuating demand is a constant challenge. When inventory decisions don’t reflect actual customer usage, companies face a frustrating cycle of stock-outs for popular items and dusty shelves for slow-movers—eventually hurting the bottom line. Mediklug, a healthcare tech firm, faced this exact issue; despite having detailed clinic-level consumption data from their EMR system, they saw a significant revenue dip in late 2025. This study explores how to bridge that gap using Demand-Driven Supply Chain (DDSC) principles. By leveraging Business Intelligence (BI), we aimed to turn Mediklug’s "data wealth" into actual insights. The research focused on three areas: identifying where demand and inventory were mismatched, building a BI dashboard to guide better purchasing, and seeing if the team would actually find the tool useful. We took a mixed-methods approach, cleaning up messy EMR data to match inventory records and interviewing the people on the front lines. The results were clear: the mismatches were systemic, but the new dashboard made demand much easier to see and manage. Most importantly, the stakeholders found the solution practical and easy to use. Ultimately, this case shows that even in complex pharmaceutical environments, BI can make "demand-driven" management a reality rather than just a theory.